Search for Large Extra Spatial Dimensions in the Dielectron and Diphoton Channels in p(p)over-bar Collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Kraus, J.; et al. (Amer Physical Soc, 2009)
We report on a search for large extra spatial dimensions in the dielectron and diphoton channels using a data sample of 1: 05 fb(-1) of p (p) over bar collisions at a center-of-mass energy of 1.96 TeV collected by the D0 detector at the Fermilab Tevatron Collider. The invariant mass spectrum of the data agrees well with the prediction of the standard model. We find the most restrictive 95% C. L. lower limits on the effective Planck scale between 2.1 and 1.3 TeV for 2 to 7 extra dimensions.